Leadership in teaching management in educational units: Case study - Sesme-Zambrano, Cruz María; Molina-Álvarez, Betsy Elizabeth; Lastenia-Pazmiño, Norma; Montesdeoca-Chávez, Martha Elizabeth; Andrade-Palacios, Magni Guiuselly (International research journal of management, IT and social sciences, 2024)
The objective of the research called Leadership in the Management of Teaching in Educational Units was to evaluate leadership in the management of teaching through the NeuroView method in Educational Units in the province of Manabí. The research adopted a quantitative, qualitative and descriptive approach with the purpose of generating information based on the results obtained. The information obtained compared the perception of the Rector/teachers / other evaluators regarding eight factors proposed by the NeuroView method. The purpose was to test the following hypotheses: Therefore, the hypothesis is tested: Ha = There are important differences between institutions that show institutional leadership in the management of teaching and those that do not show institutional leadership.